Unexpected doping effects on phonon transport in quasi-one-dimensional van der Waals crystal TiS3 nanoribbons - Chenhan Liu; Chao Wu; Xian Yi Tan; Yi Tao; Yin Zhang; Deyu Li; Juekuan Yang; Qingyu Yan; Yunfei Chen (Nature Communications, 2023)
Abstract Doping usually reduces lattice thermal conductivity because of enhanced phonon-impurity scattering. Here, we report unexpected doping effects on the lattice thermal conductivity of quasi-one-dimensional (quasi-1D) van der Waals (vdW) TiS3 nanoribbons. As the nanoribbon thickness reduces from ~80 to ~19 nm, the concentration of oxygen atoms has a monotonic increase along with a 7.4-fold enhancement in the thermal conductivity at room temperature. Through material characterizations and atomistic modellings, we find oxygen atoms diffuse more readily into thinner nanoribbons and more sulfur atoms are substituted. The doped oxygen atoms induce significant lattice contraction and coupling strength enhancement along the molecular chain direction while have little effect on vdW interactions, different from that doping atoms induce potential and structural distortions along all three-dimensional directions in 3D materials. With the enhancement of coupling strength, Young’s modulus is enhanced while phonon-impurity scattering strength is suppressed, significantly improving the phonon thermal transport.